Euphemistic Expressions in English and Kurdish - Suzan Aziz Mustafa; Salam Neamah Hirmiz Hakeem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study qualitatively describes euphemistic expressions in English and Kurdish to analyze the most common types of euphemism related to body excrement, death and sickness, sexual topics, religion, and other relevant subjects, to identify the similarities and differences between English and Kurdish in this respect. In social contexts, humans need to use a range of appropriate expressions to convey their ideas and thoughts properly; therefore, euphemisms are used by the speakers of both languages to replace words and phrases that are considered taboo, as well as to lessen the negative effect of taboo words, whose use may cause harm and humiliation to other people. This study demonstrates that while English and Kurdish languages share various aspects in the use of euphemisms, they also manifest certain distinctions